Smart Obstacle Detector for Blind Person - Rajput, Daniyal; Ahmed, Faheem; Ahmed, Habib; Ahmed Shaikh, Engr Zakir; Shamshad, Aamir (British Journal of Healthcare and Medical Research, 2014)
Smart obstacle detector helps blind people in moving and allowing them to perform their work easily and comfortably. In normal cane/stick, detection is done by the sensor. However, it is not much efficient because the blind person does not know what type of things or objects come in front of him, what is the size of that object and how far is he from the object? So it is difficult for blind person to move here and there. But SOD’s output comes in two forms i.e. sound and vibration. In SOD, we detect the object by video processing method with the help of camera. For this we have used MATLAB software and then converted the video processing output into sound. Here we have used video processing for efficient and fast detection of objects, Stick measure distance between objects and SOD stick by Ultrasonic sensor. Moreover we have connected the vibrating motor with Ultrasonic sensor. When objects come in range of ultrasonic sensor then handle of the stick will vibrates. The vibration increases if the object comes toward the stick and vibration decreases when object goes far from the stick. We can also use solar chip for operating the stick which is definitely included in the future enhancement of our research based project.